Factors Affecting Organizational Commitment Among Employees of the Propaganda and Training Department in Phongsaly Province - singchao, phonexay; DUANGVILAYKEO, Thipphavanh; SITHIRAJVONGSA, Vilat; OUNPHOUVONG, Stamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The factors influencing organizational commitment among employees are crucial for the development of an organization. Without strong organizational commitment, the organization's development may be hindered. This study aims to identify the factors that affect the organizational commitment of employees at the Propaganda and Training in Phongsaly Province, in order to promote sustainable development. The target group for this study consists of all 66 employees at the Propaganda and Training in Phongsaly Province. Questionnaires were used as the primary data collection tool. Data analysis was conducted using the SPSS version 2025 statistical program, with Multiple Regression Analysis employed to examine the relationships between the identified factors and employees' organizational commitment. The research findings indicate that factors such as personal responsibilities, management practices, organizational policies, labor costs, salaries, social welfare, and environmental factors (including colleagues) significantly influence the organizational commitment of employees at the Propaganda and Training in Phongsaly Province, with a statistical significance level of p ≤ 0.05.